Mass Migrations in Argentina: A Study on the Effects of Migrants on Electoral Outcomes - MARTIGNANO, ANDRES (2023)
In 1912, the Universal Masculine Suffrage became mandatory and secret in Argentina for natives and naturalised citizens. At the same time, the country was receiving an inflow during the ‘Age of Mass Migration’, when foreign-born people represented up to by nearly 50% of the population in some departments. These migrants had higher human capital than the Argentine natives. The aim Of this paper is to analyse the influence of immigrants on political outcomes. Using data from the Argentine Census from 1895 and 1914, my main hypothesis is that migrants carried with themselves their political preferences and generated cultural spillovers. In particular, I argue that that departments which received more migrants tended to vote more for non-Conservative candidates in the following Presidential Elections. To deal with endogeneity, I exploit the shift-share instrument, first at the national level, and then focusing on the Pampas region. I find that a higher exposure to migrants increases the Socialist Party vote share, whereas it reduces the Conservative Party vote share.